2016
DOI: 10.1038/srep34958
|View full text |Cite
|
Sign up to set email alerts
|

Stability of retained austenite in high carbon steel under compressive stress: an investigation from macro to nano scale

Abstract: Although high carbon martensitic steels are well known for their industrial utility in high abrasion and extreme operating environments, due to their hardness and strength, the compressive stability of their retained austenite, and the implications for the steels’ performance and potential uses, is not well understood. This article describes the first investigation at both the macro and nano scale of the compressive stability of retained austenite in high carbon martensitic steel. Using a combination of standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 39 publications
2
39
0
1
Order By: Relevance
“…High-carbon and chromiumcontaining steels are widely used in the current bearing industry, where the steel is often heattreated to obtain either martensitic or bainitic microstructures [2]. High-carbon martensitic steels are very well known for their high strength and hardness properties and have been used extensively for bearings over the past century [1,3]. Bainitic or martensitic microstructures are often obtained together with a retained volume fraction of austenite.…”
Section: Introductionmentioning
confidence: 99%
“…High-carbon and chromiumcontaining steels are widely used in the current bearing industry, where the steel is often heattreated to obtain either martensitic or bainitic microstructures [2]. High-carbon martensitic steels are very well known for their high strength and hardness properties and have been used extensively for bearings over the past century [1,3]. Bainitic or martensitic microstructures are often obtained together with a retained volume fraction of austenite.…”
Section: Introductionmentioning
confidence: 99%
“…Dual-phase high carbon steel has been designed to have dual-phase martensite and a retained austenite microstructure. Upon applying stress on this steel, the retained austenite transforms into martensite, which enhances its mechanical properties [4,5]. Recent studies revealed that retained austenite improved wear-resistance and sudden breakage could be minimised due to its capacity to absorb energy from impacts and loads [6].…”
Section: Introductionmentioning
confidence: 99%
“…The retained austenite phase in this high carbon steel is a meta-stable phase, which can be transferred to a martensitic structure if the required energy is provided [1]. Recent study by Rumana et al has demonstrated that the percentage of carbon in austenitic phase is lower than carbon in martensitic phase in dual-phase high carbon steel [8,9], this means that the corrosion mechanism can be initiated from either the retained austenite or martensite phase.…”
Section: Introductionmentioning
confidence: 99%
“…Dual-phase high carbon steel with a chemical composition of 0.98% C, 0.97% Mn, 0.63% Cr and a martensite structure with an average of 30% retained austenite [1] was used in this study. Samples were cut to dimensions of 6 mm × 6 mm × 3 mm using a low-abrasion cutting rate.…”
Section: Materials Preparationmentioning
confidence: 99%
See 1 more Smart Citation